India's aged :needs and vulnerabilities - Udaya S Mishra,Ed; Irudaya Rajan, S,Ed (Orient Blackswan, 2017)
India’s Aged: Needs and Vulnerabilities discusses the most vulnerable aspects of elderly life—health and well-being—under the current conditions of economic and societal change. This volume explores (a) whether the nature of living arrangements has a bearing on the health outcomes of the elderly; (b) whether the real or perceived economic dependence and financial vulnerability of the elderly is conditioned by translation of capabilities into functioning; and (c) the implied healthcare costs, which are defined as based on both actual needs and the elderly people’s own perception of their needs.